Directive Speech Acts in The King’s Speech Movie (2010) - Sari, Risma Novita; Tiyani, Elis; Hana, Hafshah; Ramadhani, Arganita (Aisyah Journal of English Language Teaching (AIJELT), 2025)
This study investigates the use of directive speech acts in The King’s Speech (2010) movie and explores their potential application in the EFL context, particularly in speaking classes. The film reflects power dynamics, collaboration, and motivational strategies that provide examples of authentic language use. The study employs the Content Analysis (CA) approach and finds 37 utterances from the main characters' interaction, which were categorized into five types of directive speech acts. The analysis revealed that the most frequently appearing in the dialogue was requesting (37.84%), followed by commanding (24.32%), inviting and suggesting (13.51% for each category), and forbidding (10.82%). These findings highlight the relevance of directive speech acts in EFL classrooms, where teacher can be used to design effective communication, foster interactive learning, and enhance students’ pragmatic competence. Integrating directive speech acts from The King’s Speech into teaching strategies can help to develop learners’ communication skills, build confidence, and support the principles of Communicative Language Teaching (CLT).